Intensity of Social Media Use In Adolescent Students And Preventive Efforts In Guidance And Counseling Services At School - Awalya Siska Pratiwi; Rahmawati, Septia (Psychosocia : Journal of Applied Psychology and Social Psychology, 2025)
The extent of social media use among adolescent students has the potential to positively and negatively affect their psychosocial development. In the context of education, social media has the potential to serve as an effective tool in the guidance and counselling process, particularly in the context of guidance and counselling services in schools. The research methodology used is descriptive research with a literature review. The literature review will provide secondary data studies which will then be used to determine the extent of adolescents' use of social media and the effectiveness of guidance and counselling interventions. The existing literature reveals a variety of effects associated with social media, both positive and negative. The efforts above have been implemented in reality group counselling, educational cinema group counselling, counselling with self-management techniques, provision of information services, home visits and classical counselling. In addition, counsellors use social media to provide guidance and counselling services, thereby facilitating the provision of assistance to counselees at present through the use of technology. The use of social media by counsellors includes implementing online counselling (e-counselling), electronic-based modules and counselling services through WhatsApp.